YB2C2: A machinable layered ternary ceramic with excellent damage tolerance. (November 2016) - Zhao, Guorui; Chen, Jixin; Li, Yueming; Li, Meishuan
Abstract: High purity bulk YB2 C2, a member of ternary rare earth metal diborodicarbides, was synthesized by an in situ hot-pressing method using YH2, B4 C, and graphite as initial materials. Physical and mechanical properties of YB2 C2, such as Young's modulus (207 GPa), shear modulus (87 GPa), bulk modulus (116 GPa), Vickers hardness (4.2 ± 0.3 GPa), three-point flexural strength (460 ± 10 MPa), and fracture toughness (4.6 ± 0.1 MPa·m 1/2 ) were characterized. The as-received YB2 C2 ceramic possesses typical layered structure, excellent damage tolerance and easy machinability. Graphical abstract: